(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Cloud Computing is known for majorly two features which makes it attractive for consumers and providers: 1. Automatic Resource Provisioning 2. Strictly following the decided QoS . Resource Provisioning needs to be dynamic and quick. Even the state of the art technology might take time in minutes to provision a VM and makes Cloud unattractive than an on-premise system. So we present a study of ASAP - A Self Adaptive Prediction System for instant demand provisioning and Cyclic Window Learning Algorithm to predict the requests. QoS is closely related to resource allocation along with but includes strictly following the SLOs. QoS prediction can help the users to select the best service as per the need for which we study ALPINE which is a system based on Bayesian Networks and another model has been discussed here. Keywords: Demand Prediction, QoS Prediction, ASAP,Cyclic Window Algorithm,ALPINE,Bayesian Networks